Tax Policy for Developing Countries - Tanzi, Vito (Economic Issues; Economic Issues ;, 2002)
Discusses important tax policy issues facing developing countries today, provides a review of the role of tax incentives, and identifies some policy challenges posed by the globalization of the world economy. Draws on country cases.